Cocaine-induced changes in behaviour and DNA methylation in rats are influenced by inter-individual differences in spontaneous exploratory activity. (June 2020) - Vaher, Kadi; Anier, Kaili; Jürgenson, Monika; Harro, Jaanus; Kalda, Anti
Background: Individual differences in behavioural traits influence susceptibility to addictive disorders. Drug addiction involves changes in gene expression, proposed to occur via DNA methylation (DNAm). Aims: To investigate DNAm changes in reward-related brain structures (nucleus accumbens (NAc), lateral habenula (LHb)) in response to cocaine exposure in rats differing in spontaneous exploratory activity. Methods: Rats were observed in the exploration box and categorised as high- (HE) or low explorers (LE). Rats were administered vehicle or cocaine (12 mg/kg, i.p.) for 7 days, followed by a 14-day withdrawal period and cocaine challenge (7 mg/kg); horizontal locomotor activity was recorded. Brain tissue was dissected after 24 h; we analysed messenger RNA (mRNA) and activity levels of epigenetic DNA modifiers (DNMTs and TETs) as well as mRNA and promoter methylation levels at selected genes previously linked to addictive behaviours. Results: The cocaine challenge dose stimulated locomotor activity in both LE- and HE rats only when administered after a repeated cocaine schedule, suggesting development of behavioural sensitisation. Quantitative polymerase chain reaction analyses demonstrated higher basal expression of Dnmt3a, Tet2 and Tet3 in the LHb of HE- vs. LE rats, and we observed differential effects of cocaine exposure on the expression and activity of epigenetic DNA modifiers in the NAc and LHb of HE- and LE rats. Furthermore, cocaine exposure differentially altered promoter methylation levels of A2A R, Ppp1cc, and Taar7b in the NAc and LHb of HE- and LE rats. Conclusions: DNAm might play a role in the HE- and LE phenotypes as well as mediate behavioural effects of LE- and HE rats in response to drugs of abuse.